Uttar Pradesh-2022 based on the facts of 2021-2022 - Lucknow, Uttar Pradesh. Information and Public Relations Department; Prasad, Sanjay, patron; Shishir; Tripathi, Anshumaan Ram, presentator & visualizer; Trivedi, Devendra Nath, tr.; Sharma, Kumkum, editorial guidance; Lucknow, Uttar Pradesh. Information and Public Relations Department (Lucknow Bharat Book Centre, 2023)
| | | | | Sharma, Kumkum, editorial guidance | Lucknow, Uttar Pradesh. Information and Public Relations
75th Azaadi ka Amrit Mahotsav
Keywords: Uttar Pradesh -- Reference annual -- 2022-; Economic development -- Uttar Pradesh -- 2022-; History -- Uttar Pradesh -- 2022-; Flora and Fauna -- Uttar Pradesh -- 2022-; Geographical features -- Uttar Pradesh -- 2022-; Cultural heritage -- Uttar Pradesh -- 2022-